Nghiên cứu vai trò của giới tính và kinh nghiệm của giám đốc đối với hoạt động xuất khẩu của doanh nghiệp sản xuất tại Việt Nam - Trần Quốc, Trung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
Compared with domestic trade, export business has more risks, and thus companies’ export revenues rely significantly on the quality of managerial decisions. In practice, each manager has his/her own psychological characteristics and personal traits which considerably determine their decision-making mechanisms. With a sample of 1,859 observations from manufacturing companies and various regression techniques such as Logit, Tobit, and OLS, this paper investigates the roles of CEO gender and experiences in companies’ export results. This study finds that companies with female CEOs are more likely to export and have higher export intensity. Besides, CEOs with more experience help their firms improve export results. These empirical findings imply that companies should create a fair mechanism for women to participate in their top-management teams instead of worrying about their performance. Moreover, this research shows that many efforts made by both public and private organizations over several years are appropriate and necessary.